GREEN BONDS ISSUANCE AND BANK STABILITY: SAFE HAVEN OR RISK UNDER CENTRAL BANK POLICY RATES? - Muizzuddin Muizzuddin; Erfan Rachmadi; Muhammad Irsyad; Cean Maria Bella (Universitas Bangka Belitung, 2026)
This study examines the effect of green bond issuance on bank stability and the moderating role of central bank policy rates. Using panel data of 1,462 banks from 29 countries during 2010-2024, the analysis applies fixed effects and dynamic System GMM to address potential endogeneity. Bank stability is measured using alternative Z-score specifications and non-performing loans. The results show that green bond issuance reduces bank stability, suggesting that the expansion of green finance may introduce short-term risks to banks. However, central bank policy rates moderate this relationship, where higher rates mitigate the adverse impact. Further analysis indicates that the negative effect is stronger during monetary tightening periods, while a U-shaped relationship suggests that more developed green bond markets may eventually support stability. These findings highlight the importance of monetary policy conditions in evaluating the financial stability implications of sustainable finance.